2020
DOI: 10.1016/j.cmet.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Lactate Controls Muscle Regeneration from Ischemia by Inducing M2-like Macrophage Polarization

Abstract: Highlights d Endothelial loss of pfkfb3 impairs ischemic muscle revascularization and regeneration d EC-derived lactate instructs MCT1-dependent macrophage functional polarization d Lactate-polarized macrophages promote muscle revascularization and regeneration d Restoring lactate levels improves macrophage polarization and recovery from ischemia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
236
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 305 publications
(246 citation statements)
references
References 81 publications
7
236
2
1
Order By: Relevance
“…It has been found that the energy metabolism of endothelial cells ECs is mainly dependent on glycolysis, and ECs-derived lactic acid can cause macrophages to be pola rized into M2-typ e. However, the loss of phosphofructokinase-2/fructose-2,6-bisphosphatase isoform 3 (PFKFB3), the glycolytic regulator, reduces lactate secretion by ECs and inhibits M2-type macrophage. In addition, MCT1 knockout inhibits M2-type macrophage differentiation (69). This suggests that the production of lactic acid in the tumor microenvironment can promote M2-type differentiation of macrophages.…”
Section: The Polarization Of Macrophages By Stromal Cellular Compartmmentioning
confidence: 98%
“…It has been found that the energy metabolism of endothelial cells ECs is mainly dependent on glycolysis, and ECs-derived lactic acid can cause macrophages to be pola rized into M2-typ e. However, the loss of phosphofructokinase-2/fructose-2,6-bisphosphatase isoform 3 (PFKFB3), the glycolytic regulator, reduces lactate secretion by ECs and inhibits M2-type macrophage. In addition, MCT1 knockout inhibits M2-type macrophage differentiation (69). This suggests that the production of lactic acid in the tumor microenvironment can promote M2-type differentiation of macrophages.…”
Section: The Polarization Of Macrophages By Stromal Cellular Compartmmentioning
confidence: 98%
“…Charts combine data from eight sections per animal, three images per section (4,5 animals per group, saline controls are combined); statistical significance was assessed by one-way ANOVA with Dunnett's Multiple Comparison Test, and *p < 0.05, **p < 0.01. myeloid cell marker (Mac 2, (Ho and Springer, 1982) to quantify inflammatory cell infiltration into lungs following epirubicin treatment ( Figure 7A). This is a critical parameter, as macrophage infiltration and activation status mediated vascular remodeling and organ microenvironment (Wenes et al, 2016;Zhang et al, 2020). The number of Mac2+ cells was systematically quantified using batch analyses and "particle analysis" function (ImageJ).…”
Section: Epirubicin Treatment Promotes Myeloid Cell Infiltration Intomentioning
confidence: 99%
“…On the other hand, blocking the tyrosine kinase (TK) VEGF receptor 2 (VEGFR2) strongly interfered with both, the process of angiogenesis and arteriogenesis (Jazwa et al, 2016). In both types of vessel growth, VEGF is supplied by leukocytes, i.e., neutrophils and monocytes (Deindl et al, 2001;Scapini et al, 2004;Morrison et al, 2014;Lautz et al, 2018;Zhang et al, 2020). But in contrast to angiogenesis, in arteriogenesis, an amplified and sustained local activation of VEGFR2 is necessary to promote endothelial cell proliferation by high levels of ERK activation (Kofler and Simons, 2015).…”
Section: Introductionmentioning
confidence: 99%